2004
DOI: 10.1002/jcu.20022
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of clubfoot

Abstract: Sonography is a promising technique for assessment and monitoring of clubfoot during treatment. The method described here yields accurate and reproducible information about the anatomy of the nonossified clubfoot, helping the orthopedic team decide on appropriate treatment steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
(19 reference statements)
1
17
0
1
Order By: Relevance
“…In the present study, mean C–C distance was found to be 3.4±2.0 mm in cases and 0.8±1 mm in controls as against a mean of 2.5±1.3 mm in cases and 1.0±1.1 mm in controls reported by Aurell et al .,8 the only author group to measure this. The C–C angle in the present study was 23.7°±10.24° in cases and 4°±6.6° in controls; Gigante et al 9. reported a mean of 20° in clubfoot and 10° in normal foot.…”
Section: Discussionsupporting
confidence: 41%
“…In the present study, mean C–C distance was found to be 3.4±2.0 mm in cases and 0.8±1 mm in controls as against a mean of 2.5±1.3 mm in cases and 1.0±1.1 mm in controls reported by Aurell et al .,8 the only author group to measure this. The C–C angle in the present study was 23.7°±10.24° in cases and 4°±6.6° in controls; Gigante et al 9. reported a mean of 20° in clubfoot and 10° in normal foot.…”
Section: Discussionsupporting
confidence: 41%
“…Second, we were unable to assess the equinus deformity sonographically with the planes used. The value of US would be enhanced with use of a posterior projection [18,32] to predict the need and possibly the timing of tenotomy. Third, we did not assess interobserver variability as we had only one senior radiologist with sufficient experience in musculoskeletal US for the readings.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, most US studies are performed in neutral or spontaneous position of the foot and in maximal correction simulating the Ponseti maneuver [3,12,14,15,17,19,28]. Although dynamic US evaluation of the foot is of great clinical significance, we wish to emphasize the difficulty for a single operator to reach and maintain a reliable correction and to perform US examination simultaneously.…”
Section: Us Assessment Of Clubfootmentioning
confidence: 98%
“…Several authors have introduced the use of US for the evaluation of clubfoot and the quantification of the deformity [9][10][11][12][13][14][15][16][17][18][19]. US also has the potential to monitor the effects of treatment [20], which is mainly nonoperative (Ponseti technique) [21][22][23][24][25][26][27].…”
Section: Us Assessment Of Clubfootmentioning
confidence: 99%